Walking speed, cognitive function and dementia risk in the English Longitudinal Study - Hackett, Ruth A.; Davies, Hilary; Cadar, Dorina; Orrell, Martin; Steptoe, Andrew (Wiley, 2018)
Background: Physical and cognitive function decline with age. Slow walking speed has been associated with negative health outcomes and dementia is often preceded by cognitive decline. This study investigated walking speed, cognitive function and the interaction between changes in these measures in relation to dementia risk.